2017
DOI: 10.1080/20002297.2017.1320193
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis suppresses invasion of Fusobacterium nucleatum into gingival epithelial cells

Abstract: Invasion of periodontal pathogens into periodontal tissues is an important step that can cause tissue destruction in periodontal diseases. Porphyromonas gingivalis is a keystone pathogen and its gingipains are key virulence factors. Fusobacterium nucleatum is a bridge organism that mediates coadhesion of disease-causing late colonizers such as P. gingivalis and early colonizers during the development of dental biofilms. The aim of this study was to investigate how P. gingivalis, in particular its gingipains, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…FadA (Fusobacterium adhesin A), is reported to be required for F. nucleatum attachment to epithelial cells and may play an important role in Fusobacterium colonization in the host [33]. Jung et al reported that the invasion of F. nucleatum into gingival epithelial cells was suppressed in the presence of P. gingivalis [35]. Our results revealed that P. gingivalis could downregulate the expression of fadA in F. nucleatum, which may be a possible explanation of their finding.…”
Section: C2 Vs C3supporting
confidence: 65%
“…FadA (Fusobacterium adhesin A), is reported to be required for F. nucleatum attachment to epithelial cells and may play an important role in Fusobacterium colonization in the host [33]. Jung et al reported that the invasion of F. nucleatum into gingival epithelial cells was suppressed in the presence of P. gingivalis [35]. Our results revealed that P. gingivalis could downregulate the expression of fadA in F. nucleatum, which may be a possible explanation of their finding.…”
Section: C2 Vs C3supporting
confidence: 65%
“…nucleatum and P. gingivalis are the major pathogens that cause periodontitis (Hajishengallis et al, 2012;Yang et al, 2014;Han, 2015;How et al, 2016). Furthermore, coinfection of F. nucleatum and P. gingivalis could enhance their adherence and invasive capacity in human gingival epithelial cells and inhibit the host innate immune response (Li et al, 2015;Jung et al, 2017). Therefore, we tested the antibacterial activity against both planktonic cultures and biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of F nucleatum did not significantly affect the amount of invading P gingivalis . Jung et al recently demonstrated that P gingivalis differentially suppresses F nucleatum invasion to immortalized gingival epithelial cells in a gingipain‐dependent manner, and that the effect resulted from specific interactions among P gingivalis, F nucleatum, and the cell type. The different results obtained by Jung et al may derive from the difference in MOI in the different studies, and Jung et al used an MOI of 500 for both bacteria, in contrast to our study that used MOI 100 for P gingivalis and MOI 10 for F nucleatum .…”
Section: Discussionmentioning
confidence: 99%